Student’s mathematical concept understanding ability in the material of functions of class XI of SMA Islam Sabilurrosyad Gasek Malang - Nuril Azizah, Rizky Wahyu (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2025)
This study aims to analyze student’s mathematical concept understanding ability on function material in class XI of SMA Islam Sabilurrosyad Gasek Malang in the 2024/2025 Academic Year. The research method used is a qualitative approach with a case study. Data were collected through interviews with teachers and students, classroom observations, and concept understanding tests. Interviews were conducted to explore factors that influence student understanding, observations were used to see student interactions with the material and teaching methods applied, and tests were used to identify student misconceptions. The collected data were analyzed to determine the main themes related to student’s difficulties in understanding the concept of functions and the misconceptions that occurred. The study results showed that there were difficulties for students in understanding the concept of functions, which were caused by factors such as ineffective teaching methods and a lack of practice. Based on these findings, it is recommended that teachers improve their teaching methods and provide more varied exercises to improve student understanding. The implications of this study show the importance of an interactive and contextual teaching approach in conveying mathematical concepts. As a practical recommendation, teachers are advised to use visual learning media and provide constructive feedback to help students build a deeper understanding of concepts.